The construction of Congolese-Belgian relations in apologies. A discourse analysis of letters over colonial past - Simona Lastrego; Sara Aguirre; Nicolas Van der Linden (Quaderns de Psicología)
Apologies have attracted the attention of various social sciences’ disciplines, suggesting the need for political figures to apologize for ingroup’s historical injustices. Despite these expectations, Belgium has not yet offered public apologies for its colonial past in Congo. In 2019, a Belgian company launched a competition offering the possibility for Belgian citizens to write an apology for the country’s colonial past. In this paper, we analyze five letters selected by the company and examine how authors describe the ingroup and the outgroup in order to understand Belgian and Congolese present relationships. Drawing on discursive psychology, we looked at how the two social groups are constructed by means of regularity and variability in the authors’ use of discursive devices. Results show that the majority of the discursive devices are used to maintain a distinction between the two. Similarities and differences among letter in terms of intergroup relations are discussed.